A novel missense variant in the nuclear localization signal of POU4F3 causes autosomal dominant non-syndromic hearing loss - Lin, Yin-Hung (Sci Rep, 2017)
Autosomal dominant non-syndromic hearing loss (ADNSHL) is genetically heterogeneous with more than 35 genes identified to date. Using a massively parallel sequencing panel targeting 159 deafness genes, we identified a novel missense variant of POU4F3 (c.982A>G, p.Lys328Glu) which co-segregated with the deafness phenotype in a three-generation Taiwanese family with ADNSHL. This variant could be classified as a “pathogenic variant” according to the American College of Medical Genetics and Genomics guidelines. We then performed subcellular localization experiments and confirmed that p.Lys328Glu compromised transportation of POU4F3 from the cytoplasm to the nucleus. POU3F4 p.Lys328Glu was located within a bipartite nuclear localization signal (NLS), and was the first missense variant in bipartite NLS of POU4F3 validated in functional studies. These findings expanded the mutation spectrum of POU4F3 and provided insight into the pathogenesis associated with aberrant POU4F3 localization.